Beyond Chloride Brines: Variable Metabolomic Responses in the Anaerobic Organism Yersinia intermedia MASE-LG-1 to NaCl and MgSO4 at Identical Water Activity - Schwendner, Petra; Bohmeier, Maria; Rettberg, Petra; Beblo-Vranesevic, Kristina; Gaboyer, Frédéric; Moissl-Eichinger, Christine; Perras, Alexandra K.; Vannier, Pauline; Marteinsson, Viggó T.; Garcia-Descalzo, Laura; Gómez, Felipe; Malki, Moustafa; et al. (Frontiers in Microbiology, 2018)
Growth in sodium chloride (NaCl) is known to induce stress in non-halophilic microorganisms leading to effects on the microbial metabolism and cell structure. Microorganisms have evolved a number of adaptations, both structural and metabolic, to counteract osmotic stress. These strategies are well-understood for organisms in NaCl-rich brines such as the accumulation of certain organic solutes (known as either compatible solutes or osmolytes). Less well studied are responses to ionic environments such as sulfate-rich brines which are prevalent on Earth but can also be found on Mars. In this paper, we investigated the global metabolic response of the anaerobic bacterium Yersinia intermedia MASE-LG-1 to osmotic salt stress induced by either magnesium sulfate (MgSO4) or NaCl at the same water activity (0.975). Using a non-targeted mass spectrometry approach, the intensity of hundreds of metabolites was measured. The compatible solutes L-asparagine and sucrose were found to be increased in both MgSO4 and NaCl compared to the control sample, suggesting a similar osmotic response to different ionic environments. We were able to demonstrate that Yersinia intermedia MASE-LG-1 accumulated a range of other compatible solutes. However, we also found the global metabolic responses, especially with regard to amino acid metabolism and carbohydrate metabolism, to be salt-specific, thus, suggesting ion-specific regulation of specific metabolic pathways.